The Influence Of Work Motivation And Job Satisfaction To Employee Organizational Commitment BPR Nusamba Singaparna - Suriyanti; Dadang Heri Kusumah (Institute of Computer Science (IOCS), 2022)
Appropriate human resources are very important requirement to create a competitive advantage for a company. The success or failure of company cannot be separated from organizational commitment. This study uses a non-probability sampling technique. The hypothesis analysis method used is multiple. Linear regression to prove the hypothesis that this research has met the validity test, reliability test, classical assumption test and then processed to get the regression equatoin. The results of the t-test research show that the t-count value is greater than t-table (8,173 > 1,692) with a significant value below 0.05, which is 0.000. Therefore, Ha is accepted, meaning that the work motivation variable partially has a significant effect on the organizational commitment variable. The job satisfaction variable obtained the result of the t-test with a t-count value greater than t-table (3,387 > 1,692) with a significant value below 0.05, that is 0.001, therefore it is accepted, meaning that the job satisfaction variable partially has a significant effect on organizational commitment and it can be said that motivation work and job satisfaction together have a significant effect on organizational commitment.